2017
DOI: 10.1186/s13068-017-0738-8
|View full text |Cite
|
Sign up to set email alerts
|

Engineering vesicle trafficking improves the extracellular activity and surface display efficiency of cellulases in Saccharomyces cerevisiae

Abstract: BackgroundCellulase expression via extracellular secretion or surface display in Saccharomyces cerevisiae is one of the most frequently used strategies for a consolidated bioprocess (CBP) of cellulosic ethanol production. However, the inefficiency of the yeast secretory pathway often results in low production of heterologous proteins, which largely limits cellulase secretion or display.ResultsIn this study, the components of the vesicle trafficking from the endoplasmic reticulum (ER) to the Golgi and from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…Tang et al [75] improved the surface display efficiency of recombinant a-agglutinin fusion with Clostridium thermocellum endoglucanase CelA and S. fibuligera β-glucosidase BGL1 by engineering vesicle trafficking. Sec12, Sec13, Erv25, and Bos1 proteins, involved in vesicle trafficking from the ER to the Golgi, and Sso1, Snc2, Sec1, Exo70, Sec4, and Ypt32 proteins, involved in vesicle transport from the Golgi to the plasma membrane, were overexpressed in strains expressing CelA/a-agglutinin and BGL1/a-agglutinin.…”
Section: Engineering Of Cell Wall Surface and Secretory Mechanismsmentioning
confidence: 99%
“…Tang et al [75] improved the surface display efficiency of recombinant a-agglutinin fusion with Clostridium thermocellum endoglucanase CelA and S. fibuligera β-glucosidase BGL1 by engineering vesicle trafficking. Sec12, Sec13, Erv25, and Bos1 proteins, involved in vesicle trafficking from the ER to the Golgi, and Sso1, Snc2, Sec1, Exo70, Sec4, and Ypt32 proteins, involved in vesicle transport from the Golgi to the plasma membrane, were overexpressed in strains expressing CelA/a-agglutinin and BGL1/a-agglutinin.…”
Section: Engineering Of Cell Wall Surface and Secretory Mechanismsmentioning
confidence: 99%
“…This was achieved through the utilization of various molecular techniques that lead to the optimization of signal sequences, upregulation of ER folding, modification of vesicle transport, and deletion of host proteinases as discussed in detail by Haan, et al [112]. A recent example of this in relation to the role of surface display for efficient lignocellulose utilization has been demonstrated by Tang, et al [113]. Where the localization and co-display of the C. thermocellum endoglucanase (CelA) along with a S. fibuligera β-glucosidase (BGL) was improved by the over-expression of various vesicle trafficking components.…”
Section: On the Enzyme Functionality And Display Efficiencymentioning
confidence: 99%
“…Where the localization and co-display of the C. thermocellum endoglucanase (CelA) along with a S. fibuligera β-glucosidase (BGL) was improved by the over-expression of various vesicle trafficking components. Furthermore, their results have shown that there is a protein-specific effect, which limit the vesicle trafficking pathway with respect to the heterologous protein being localized; this provides an insight on how to improve surface display efficiency tailored to the protein of interest [113]. In the semi-rational approach, the genes in the cell wall environment are targeted instead of those in the secretory pathway.…”
Section: On the Enzyme Functionality And Display Efficiencymentioning
confidence: 99%
“…Moreover, S. cerevisiae is a generally recognized as a safe (GRAS) organism, which makes it a favorable for use in the production of biopharmaceuticals 67,68 . Unfortunately, the natural capacity of S. cerevisiae secretory pathway is relatively limited and, thus, mechanisms that improve secreted protein production would be of significant benefit.…”
Section: Unlike Yeast However Human Transcripts Contain Larger Portmentioning
confidence: 99%